2020
DOI: 10.3390/su12197922
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Interventions for Non-Specific Low Back Pain in Tactical Populations: A Systematic Review of Randomized Controlled Trials

Abstract: Limited evidence exists about non-specific low back pain (NSLBP) interventions among tactical personnel (police officers, firefighters, or army forces). The aim was to identify and systematically review the findings of randomized control trials (RCTs) investigating conservative interventions for the treatment NSLBP in tactical personnel. A search of seven databases for randomized controlled trials RCTs were conducted. Two independent reviewers extracted data and assessed the risk of bias (PEDro scale). Five RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A systematic review of tactical populations (i.e., police, firefighters, and military personnel), including five randomized clinical trials testing conservative treatments for CLBP (i.e., exercise). Still, none of them included police and firefighters or used the telerehabilitation approach [27]. Stigma, geographic barriers, and lack of worker health sectors often prevent police and firefighters professionals from engaging in these evidence-based treatments.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of tactical populations (i.e., police, firefighters, and military personnel), including five randomized clinical trials testing conservative treatments for CLBP (i.e., exercise). Still, none of them included police and firefighters or used the telerehabilitation approach [27]. Stigma, geographic barriers, and lack of worker health sectors often prevent police and firefighters professionals from engaging in these evidence-based treatments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of exercise-based telerehabilitation strategies on biopsychosocial outcomes in police officers and firefighters with CLBP is not entirely established. Previous systematic review of non-conservative interventions in tactical populations (i.e., police, firefighters, and military personnel) showed that interventions using telerehabilitation approach in this population are scanty [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent epidemiological survey reported that the 3-month and 12-month prevalence of LBP for military helicopter pilots was as high as 42.3 and 48.1% ( Posch et al, 2019 ), respectively. Meanwhile, aviation medicine research showed that early detection of LBP and timely implementation of medical intervention prior to the observation of apparent symptoms, such as physiotherapy and neuromuscular electrical stimulation, could particularly be beneficial to the health and well-being of pilots ( Palmer and Bovenzi, 2015 ; Alrwaily, 2017 ; Marins et al, 2020 ). Additionally, objective assessment of LBP severity is helpful for implementing appropriate and specific treatment.…”
Section: Introductionmentioning
confidence: 99%